Penerapan Senam Irama Untuk Meningkatkan Motorik Kasar Anak 4-5 Tahun di TKQ Tamrinusshibyan - Siti Badriah; Ine Nirmala; Feronica Eka Putri (Jurnal Ilmiah Wahana Pendidikan, 2022)
This research is motivated by the lack of physical motoric development of children with rhythmic gymnastics activities This study aim to develop child’s gross motor skills through rhytmic gymnastice activities On the following indikator, strength, balance, and coordination. The subjeks of this study were 21 children of group A TKQ Tamrinusshibyan Karawang district and the researh method used is classroom action research (CAR). The result of the study show that there is a process of gros motor development in children through rythmic gymnastics actitivities. These results can be seen from the pre-observation, activities in cycle 1 and cycle ll. The pre-observed child’s strenghth indicator is 35%, in the first cycle it is 55% and the second cycle is 75%, meaning that the are is a development in the child’s streght of 37,5% that there is a development of 45% in the child’s balance indikator of 32,5% in pre-observation, in cycle I it was 55%, and cycle ll was 77,5% so that the development of children’s coordination in cycle ll it was 75% so that the increase reached 41%. With activities. Rhyhmic gymnastics activities can develop gross skills of group A children at TKQ Tamrinusshibyan Karawang.